Perlindungan Hukum bagi Konsumen atas Perbuatan Overclaim Pelaku Usaha pada Produk Skincare - Nadia Firda Ayu Fernanda (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The skincare industry is growing very rapidly along with increasing public awareness of the importance of proper skin care. However, in marketing their products, many business actors make exaggerated claims regarding product benefits that are often not supported by facts or scientific evidence. The study aims to analyze the application of consumer legal protection in overclaiming actions carried out by business actors on skincare products from the perspective of Law Number 8 of 1999 concerning Consumer Protection. The research method applied is the normative juridical method with a statutory approach and a conceptual approach. In this study, the practice of overclaiming carried out by business actors on skincare products is contrary to applicable legal provisions, namely Articles 8 and 10 of the Consumer Protection Law. These articles prohibit business actors from providing misleading information about a product and violate consumer rights as defined in Article 4 of the Consumer Protection Law. Although normatively the law has provided sufficient protection for consumers, its implementation in the field still faces many challenges. Supervision from the government and related institutions such as the BPOM is very necessary to ensure business actors' compliance with applicable regulations. Firm and consistent law enforcement is also needed to make business actors more responsible in providing information to consumers and to foster healthy and ethical skincare industry climate.